Relaxation Techniques in Trauma Recovery for Children with Disabilities Experiencing Sexual Violence - Trikora, Dayne (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Trauma resulting from sexual violence has intricate psycho-emotional and physiological effects on children with disabilities. This study was conducted to investigate the effect of relaxation techniques on anxiety symptoms, trauma symptoms, and sleep quality and social interactions. This was a Single Subject Design (SSD), A-B-A-B study with two subjects, a girl with physical disabilities and a boy with mild intellectual disabilities. The intervention consisted of breathing relaxation techniques, progressive muscle relaxation (PMR) and positive visualization. The findings also revealed that mean CAS scores during the intervention phase were significantly lower than mean scores in the observational phase from the pre-test to post-test, along with fewer nightmares and tantrum complaints. Sleep quality and in-person social interactions also improved significantly. Effectiveness of intervention was also analyzed using ‘Percentage of Nonoverlapping Data (PND’) showing 85% for Subject 1 and 80% for Subject 2, meaning a high level of intervention effectiveness. This reinforces the need for a comprehensive, family and community approach, and customized interventions. These findings can serve as a basis for the formulation of more inclusive and evidence-based rehabilitation programs for children with trauma secondary to sexual violence.